2016
DOI: 10.1021/acs.jafc.6b02187
|View full text |Cite
|
Sign up to set email alerts
|

Rice (Oryza sativa) Laccases Involved in Modification and Detoxification of Herbicides Atrazine and Isoproturon Residues in Plants

Abstract: Atrazine (ATR) and isoproturon (IPU) as herbicides have become serious environmental contaminants due to their overuse in crop production. Although ATR and IPU in soils are easily absorbed by many crops, the mechanisms for their degradation or detoxification in plants are poorly understood. This study identified a group of novel genes encoding laccases (EC 1.10.3.2) that are possibly involved in catabolism or detoxification of ATR and IPU residues in rice. Transcriptome profiling shows at least 22 differential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(44 citation statements)
references
References 52 publications
0
44
0
Order By: Relevance
“…Previous evidence has shown that the expression of HPPD responded to oxidative stress in barley leaf because it was induced by senescence, methyl jasmonate, ethylene, hydrogen peroxide and herbicide; paraquat and 3-(3,4-dichlorophenyl)-1,1-dimethylurea [ 72 ]. Furthermore, a report on the expression of two rice laccase ( LAC ) genes (LOC_Os01g63180 and LOC_Os12g15680), which were identified as HT salt-responsive DEG here, in yeast cells suggested that the laccases played roles in atrazine and isoproturon herbicide detoxification [ 73 ]. In Arabidopsis, atlac1 and atlac2 mutants exhibited deficient root elongation under polyethylene glycol (PEG) treatment, while the atlac8 mutant showed early flowering and the atlac15 mutant showed abnormal seed color.…”
Section: Discussionmentioning
confidence: 99%
“…Previous evidence has shown that the expression of HPPD responded to oxidative stress in barley leaf because it was induced by senescence, methyl jasmonate, ethylene, hydrogen peroxide and herbicide; paraquat and 3-(3,4-dichlorophenyl)-1,1-dimethylurea [ 72 ]. Furthermore, a report on the expression of two rice laccase ( LAC ) genes (LOC_Os01g63180 and LOC_Os12g15680), which were identified as HT salt-responsive DEG here, in yeast cells suggested that the laccases played roles in atrazine and isoproturon herbicide detoxification [ 73 ]. In Arabidopsis, atlac1 and atlac2 mutants exhibited deficient root elongation under polyethylene glycol (PEG) treatment, while the atlac8 mutant showed early flowering and the atlac15 mutant showed abnormal seed color.…”
Section: Discussionmentioning
confidence: 99%
“…Laccases from other plants have been proposed and successfully tested for dye degradation using suspension cells and purified laccases [8690]. Huang et al [91] identified laccases in rice ( Oryza sativa ), possibly involved in atrazine and isoproturon (herbicides) catabolism or detoxification. The two Oryza sativa laccases expressed heterologously in P. pastoris , led to the increased resistance of cells to atrazine and isoproturon, suggesting that some of the laccases could be involved in detoxification or degradation of these herbicides [91].…”
Section: Sources Of Laccases That Are Useful In Water Bioremediationmentioning
confidence: 99%
“…Plant laccase families are even larger than fungal laccase families. For example, there are at least 22 laccase genes in rice ( Oryza sativa ) (Huang et al, 2016). The model plant, Arabidopsis thaliana , has 17 members in its laccase gene family, which play several roles in plant growth and development, based on mutant characterization and expression profiling (Cai et al, 2006; Turlapati et al, 2011).…”
Section: Natural Laccase Producersmentioning
confidence: 99%